Spectrum DAC/ADC board / Salmah Omar and Hasmah Md Derus - Omar, Salmah; Md. Derus, Hasmah (1985)
This report is on the project of Spectrum DAC/ ADC board was prepare and submitted in partial fulfillment if the final year course for the award of Dip. in Electronic Engineering, Mara Institute of Technology